Clinical outcomes of myeloid/lymphoid neoplasms with fibroblast growth factor receptor-1 (FGFR1) rearrangement. Issue 8 (14th September 2018) - Umino, Kento; Fujiwara, Shin-ichiro; Ikeda, Takashi; Toda, Yumiko; Ito, Shoko; Mashima, Kiyomi; Minakata, Daisuke; Nakano, Hirofumi; Yamasaki, Ryoko; Kawasaki, Yasufumi; Sugimoto, Miyuki; Yamamoto, Chihiro; et al.
ABSTRACT: Objective: Myeloid/lymphoid neoplasms with fibroblast growth factor receptor-1 ( FGFR1 ) rearrangement are hematopoietic stem cell disorders with a poor prognosis, but no established standard therapy.Methods: We experienced a patient with T-lymphoblastic lymphoma (LBL) associated with FGFR1 rearrangement who underwent cord blood transplantation, but died of pulmonary complication. We collected the clinical data of patients with FGFR1 rearrangement from the medical literature and analyzed 45 patients, including our patient.Results: The primary diagnoses were myeloproliferative neoplasm (MPN) or myelodysplastic syndromes (MDS) in 14 and acute leukemia or LBL in 31. In MPN and MDS patients, the cumulative incidence of transformation to blast phase (BP) at 12 months was 46.2%. The 1-year overall survival (OS) from diagnosis in all cases was 43.1%. With regard to the impact of treatment response on survival, the achievement of complete response with a landmark at 2 months after diagnosis of BP was associated with a superior OS (40.0% vs. 26.0% P = 0.011 for 1-year OS from BP). Allogeneic hematopoietic stem cell transplantation (HSCT) was performed in 13 patients, and the 1-year OS from allogeneic HSCT was 61.5%. The hazard ratio for mortality was 0.34 (95% CI, 0.08–1.51, P = 0.15) for allogeneic HSCT treated as a time-dependent covariate, which suggests that allogeneic HSCT may confer a clinical benefit.Conclusion : The further accumulation of clinical data is needed to determine the optimal therapeutic approach for these neoplasms.